PENGHITUNGAN, PENYETORAN, PELAPORAN, DAN PENCATATAN PPH UNIFIKASI DENGAN SISTEM CORETAX PADA PT XYZ - Gunawan, Enggun; Fitria, Nabiilah Putri; Fibriyadi, Istna (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the calculation, payment, reporting, and recording of Unified Income Tax (PPh) using the Coretax system at PT XYZ. The Coretax system is a digital tax platform developed by the Directorate General of Taxes to improve the efficiency and accuracy of tax administration. The research method used was a case study with a descriptive qualitative approach, which included direct observation, interviews, and documentation at PT XYZ. The results indicate that the implementation of the Coretax system helps the company calculate Unified Income Tax more accurately and efficiently, and facilitates timely tax payment and reporting. Furthermore, tax recording becomes more systematic and well-documented. However, challenges remain in terms of user adaptation and technical system constraints. Therefore, ongoing training and technological infrastructure improvements are key to optimizing the Coretax system within the company environment. This research contributes to a better understanding of the integration of digital technology in corporate tax administration.